ANALISIS JENIS DAN PENYEBAB KECACATAN PRODUK CHOCOMIX DI CV GRIYA COKELAT NGLANGGERAN, DESA NGLANGGERAN, KABUPATEN GUNUNGKIDUL, DIY - Chofifah Endar Nuraziz; Titisari Juwitaningsih (Journal of Food Technology and Agroindustry, 2021)
Quality is important for a company because it is related to customer satisfaction and the name of the company. The production process must produce quality products in accordance with the standards set by a company. Therefore, quality control activities are carried out as an effort to maintain quality so that there are no defective products and deviate from the established standards. This study aims to determine the types and causes of defects in Chocomix products at CV Griya Cokelat Nglanggeran. The research object used was 5 Chocomix variants, namely Chocomix-original, Chocomix-classic, Chocomix-tawa, Chocomix-ffee, and Chocomix-ice with data analysis methods using Pareto diagrams, fishbone diagrams, and descriptive statistical methods. The results showed that there were 3 types of defects that occurred in Chocomix products, namely 79% broken packaging, no 18% AKG sticker, and 3% net non-compliance with the priority of defects, namely the type of broken packaging. Then the main factor causing defects is the method factor, with the problem being the cause because the entire packaging process is still done manually so that the possibility of defects is greater